Development Communication for The Empowerment of People’s Weaving Business in Timor Tengah Selatan Regency - Kuncoro, Agus; Sumardjo, Sumardjo; Lubis, Djuara P; Agusta, Ivanovich (Jurnal Indonesia Sosial Sains, 2023)
The purpose of this research is to describe the conditions and problems faced by the people in South Central Timor (TTS) Regency, especially those who do people's weaving businesses and to analyze the development communication that occurs in the weaving group assisted by the Trade, Industry and MSME Office of TTS Regency. This study uses a qualitative method with an interpretive approach. Furthermore, the author conducted direct interviews with a group of people's weaving craftsmen under the auspices of the Department of Trade, Industry, Cooperatives and SMEs in TTS Regency. This study found that development communication in an area has not led to empowerment. On the other hand, power dynamics between parents and young people will continue to be a feature of a society. Therefore, development communication must be carried out to facilitate different local cultural communication structures, in order to encourage empowerment not only for parents but also for the younger generation.